Covered Interest Parity in long-dated securities - Olav Syrstad (Norges Bank, 2020)
This paper investigates the validity of Covered Interest Rate Parity (CIP) in longdated fixed income securities. I show that common measures of CIP rely on trading strategies subject to rollover risk and credit risk, or fail to fully account for the trading costs. Hence, roundtrip CIP profit is generally not possible to reap when the trade is risk-free and all costs are taken into account. In particular, short-selling costs (haircuts and lending fees) and differences in funding spreads across currencies allow for substantial deviations from common measures of CIP without implying arbitrage opportunities. In contrast to recent research, my results lend little support to the view that stricter banking regulations have led to persistent arbitrage opportunities in long-dated fixed income markets.
hdl:11250/2690064
Keywords: E43; F31; G15; 330; Covered Interest Parity; FX-swaps; Libor; Corporate bonds; Arbitrage; Securities Lending